Self-Reported Oral Health Attitudes and Behavior of Dental and Medical students, Yemen - Halboub, Esam S.; Al-Maweri, Sadeq A.; Al-Jamaei, Aisha A.; Al-Wesabi, Mohammed A.; Shamala, Anas; Al-Kamel, Ahlam; Al-Sharani, Amani; Eissa, Nassar (Canadian Center of Science and Education (CCSE), 2016)
Objectives: To assess self-reported oral health attitudes and behavior among undergraduate dental and medical students, and to analyze the variations in oral health attitudes based on gender, level of education, study discipline, academic average, and type of university. Methods: A self-administered questionnaire based on the Hiroshima University-Dental Behavioural Inventory (HU-DBI) was distributed to 1269 undergraduate dental and medical students at two universities (one public and one private) in Sana'a, Yemen. Results: Overall, the mean questionnaire score for the total sample was markedly low (4.911.58), with no significant difference between dental and medical students (P>0.05). Females had better oral health attitudes and behavior, especially towards visiting the dentist, tooth-brushing habits and oral hygiene practices (P<0.05). Students attending the public university had better oral health attitudes and behaviors than those attending the private university (P=0.049). On the other hand, no significant associations were observed between students' oral health attitudes/behavior and level of education and academic performance (P>0.05). Conclusion: Yemeni dental and medical students have shown markedly poor oral health attitude and behavior. Further studies are required to reveal possible shortcoming in these schools' education process. Dental and medical curricula should emphasize the importance of proper oral hygiene, and further participation of medical and dental students in oral hygiene seminars is highly encouraged.